Primary extra-gastrointestinal stromal tumor of retroperitoneum: Clinicopathologic characteristics and prognosis of six cases - Lin, Jiaxin; Liao, Weilin; Wang, Jiahao; Li, Wenjuan; Tang, Xin; Li, Hongming; Yi, Xiaojiang; Lu, Xinquan; Chen, Zhaoyu; Zhu, Bosen; Feng, Xiaochuang; Diao, Dechang (Frontiers in Oncology, 2023)
Aim: This study investigates the clinicopathological features and prognostic genic biomarker factors of primary retroperitoneal extra-gastrointestinal stromal tumors (EGISTs). Methods: The clinicopathological data of six patients with primary retroperitoneal EGIST were analyzed, including cell type (epithelioid or spindle), mitoses, and the presence of intratumoral necrosis and hemorrhage. Mitoses were counted and summed from 50 high power fields (HPFs). Mutations of exons 9, 10, 11, 13, 14, and 17 of the C-kit genes and those of exons 12 and 18 of the PDGFRA gene were examined. Follow-up was performed via telephone, and all outpatient records were reviewed. The last follow-up date was February 2022, the median follow-up was 27.5m and the postoperative status, medication, and survival of the patients were recorded. Result: The patients were treated with radical intent. Four cases (patients 3, 4, 5, and 6) underwent multivisceral resection for encroachment on the adjacent viscera. The postoperative pathological results demonstrated that all biopsy specimens were negative for S-100 and desmin, and positive for DOG1 and CD117. Additionally, four patients (case 1, 2, 4, and 5) were positive for CD34, four (case 1, 3, 5, and 6) were positive for SMA, four (case 1, 4, 5, and 6) had >5/50 HPFs, and three (case 1, 4, and 5) had Ki67 ＞5%. According to the modified National Institutes of Health (NIH) guidelines, all patients were graded as high-risk cases. By exome sequencing, exon11 mutations were detected in the six patients, while exon10 mutations were detected in two cases (patients 4 and 5). The median follow-up time was 30.5 (11–109) months, with only one fatality at 11 months. Conclusion: Retroperitoneal EGIST is a rare mesenchymal tumor that is difficult to distinguish from other retroperitoneal tumors. To diagnose this highly malignant tumor, low-threshold suspicion is necessary, and Kit and PDGFRA gene mutations should be routinely tested to confirm the diagnosis and guide subsequent treatment.